Development of a novel media for constructed wetlands systems for treating solar septic tank effluent - Pitchaya Saetan; Thammarat Koottatep; Nguyen, Thi Kim Oanh; Xue, Wenchao; Tatchai Pussayanavin; Bangchak Petroleum Public Company Limited, Thailand; Royal Thai Government Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2021)
The solar septic tank which was an improvement of a conventional septic tank was regarded to be an effective on-site sanitation technology. However, the solar septic tank effluent does not still meet the national discharged standards of Thailand. Therefore, the post-treatment which is the constructed wetland is necessary for wastewater treatment to follow the Thailand standard. The vertical wetland in this experiment consists of the novel media, the appropriate type of plant, and vertical flow pattern. Moreover, these operating systems were installed with the building wall to overcome the limitations of huge area requirements. For the best media, they consist of zeolite, bentonite, laterite soil, and coffee ground. Its result of phosphorus concentration at 3, 6, 9 mg/L was 78.38, 89.60, and 94.28%, respectively. In terms of the optimum HRT, the highest value in this experiment of removal performance of COD, NH3-N, and TP is HRT of 36 hours. Finally, the comparison performance between types of plant in reactors present that M2, Coleus system provided the highest removal performance of COD, TKN, and TSS in phase 1. For the experiment in phase 2, the highest treatment capacity of COD, TSS, and VSS was M2, Coleus system. The consequence of the plant uptake capacity of TP and TN presents that M2, Coleus system was the highest performance. The most appropriate type of plant for the vertical wetland was Coleus which was installed in the M2 system.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Environmental Engineering and Management
Thesis (M. Eng.) - Asian Institute of Technology, 2021
Keywords: Wastewater -- Treatment; Constructed wetlands -- Thailand; Septic tanks -- Thailand -- Management